Potential Application of Downhole Gas Compressor to Improve Productivity for Gas Reservoir - Hossain, Mofazzal; Mohd Ismail, Mohd Dali (SPE, IPTC, 2013)
Downhole Gas Compression (DGC) is the new form of Artificial Lift Technology used to increase the productivity of gas wells. Surface compressors are commonly used to reduce the pressure at the wellhead, which in turn reduces flowing bottom hole pressure, and boost the well productivity for a gas well especially during its decline phase when average reservoir pressure falls to a value equal to the pressure in the wellbore imposed by the sales line at the surface, plus the pressure losses that occur in the gathering system and the tubing. This conventional technique is not very efficient for the gas wells that produce significant amount of liquid (water or condensate), since this liquid needs to be separated before reaching the gas compressor. In addition, it also requires additional space for compressor assembly into the well, which may be very challenging for wells in offshore and subsea environment. As an alternative to surface compressors, downhole gas compressors technique can be applied to increase the well productivity, especially gas wells in offshore and subsea environment. Some study claimed that this new technology could: increase more than 30% of gas production; resolve many multiphase related issues; and delay the onset of liquid loading. However, numerous challenges associated with design, development and implementation of this new technology are not well understood or documented.This study has been focused to understand the key concepts of the technology and explore its potential application for increasing well productivity of gas wells through sensitivity studies. This paper presents principles mechanisms including theoretical background of DGC techniques, and results of sample case studies based on sensitivity analysis with aims to identify key factors to be considered for successful deployments of DGC into a gas well for natural gas reservoir. The paper also summarizes key findings which may be used as potential guidelines while considering for possible implementation of DGC technique during field development planning.